The tyranny of the two-party system - Disch, Lisa Jane (Columbia University Press, 2002)
Democrats and Republicans: is this duopoly an immutable and indispensable aspect of American democracy? In this text Lisa Jane Disch argues that it is not. This is an impassioned and eloquent argument in favour of third parties.
Keywords: Political parties -- United States.; Two-party systems -- United States.; Bipartisme -- États-Unis.; POLITICAL SCIENCE -- Political Process -- Political Parties.; POLITICAL SCIENCE -- American Government -- National.; Political parties; Two-party systems; United States